Uji Keefektifan Insektisida Spinetoram Terhadap Ulat Grayak (Spodoptera frugiperda J.E.Smith): The Effectiveness Test of Spinetoram Insecticide Against Fall Armyworm (Spodoptera frugiperda J.E.Smith) - Asa Alfina Fitriani; Dulbari; Ni Siluh Putu Nuryanti (Politeknik Negeri Lampung, 2023)
Fall Armyworm pests are polyphage pests that attack food and horticultural crops and can cause very large losses. The purpose of the efficacy test is to determine the effectiveness of insecticides with active ingredients Spinetoram in an effort to reduce the attack of Spodoptera frugiperda larvae and determine the symptoms of caterpillar death against the active ingredient Spinetoram. This activity is carried out in Karawang Research Farm PT Corteva Agriscience Indonesia (Research and Development Karawang) located at Jalan Selang, Ciwaringin, Lemahabang, Karawang Regency in May 2023. The activities carried out include rearing FAW in the preparation of test insects, grouping test insect larvae, and making active ingredient solutions, then the method used is the bioassay method by dipping young corn leaves into the active ingredient solution and drying the wind. Mortality observations were made ranging from 3, 6, 9, 12, 24, and 48 HAA to determine LC50 and LC95. Based on the results of the discussion, it can be concluded that LC50 is obtained at 3 JSA, namely P1 (0.47 ml /L) of 60%, P2 (0.59 ml/L) is 64%, P3 (0.71 ml/L) is 74%, and P4 (0.83 ml/L) is 66%. LC95 was obtained at 24 HAA for P1 (0.47 ml/L) and P2 (0.59 ml/L) at 98%. In 48 HAA, all treatments were obtained at 100%. Symptoms of death are very specific to the body of the larva Spodoptera frugiperda on P4. Keyword: Spinetoram, Spodoptera frugiperda, Bioassay.